Predicting the Mental Health of Mothers of Children with Intellectual Disabilities Based on Emotion Regulation Strategies with the Mediating Role of Emotional Intelligence - Dadvar, Hadis; Mahmoudiyan Dastnaee, Tahereh (International Journal of Education and Cognitive Sciences, 2025)
Purpose: This study aimed to predict the mental health of mothers of children with intellectual disabilities based on emotion regulation strategies with the mediating role of emotional intelligence. Methods and Materials: The present study is applied in terms of its objective and falls under the category of descriptive-correlational research in terms of method and nature. The study population consisted of mothers attending rehabilitation centers in District 5 of Tehran. Based on the formula proposed by Tabachnick and Fidell (2007), 215 individuals were selected as the sample, and questionnaires were distributed among the sample group using convenience sampling. The data collection instruments in this study included the Goleman Emotional Intelligence Questionnaire (2000), the Gross and John Emotion Regulation Strategies Questionnaire (2003), and the Keyes Mental Health Questionnaire (2002). Data analysis was performed using AMOS software. Findings: The results indicated that the mental health of mothers of children with intellectual disabilities could be predicted based on emotion regulation strategies, with a coefficient of 0.32. Moreover, emotional intelligence played a mediating role in the relationship between emotion regulation strategies and mental health, with a coefficient of 0.57. Conclusion: The obtained results can be utilized by family system policymakers to develop programs and interventions aimed at enhancing the mental health of mothers of children with intellectual disabilities.